Investor and (Un)Accountability of The Supervisor in Self-Construction of a Single-Family House - Mojca Klemenčič Manič; Zoran Cunk; Štefan Bojnec (Central European Public Administration Review)
The paper addresses the role and importance of a supervisor and his controlling bodies in self-construction of a single-family house. We study his accountability in actions, which must be in accordance with both statutory provisions and ethical-moral rules of social responsibility. In determining his accountability for construction execution we mainly focus on the findings of his monitoring bodies, the professional organizations (the Slovenian Chamber of Engineers and the Chamber of Architecture and Environmental Planning of Slovenia) and the building inspectorate. The Construction Act and certain rules, which clearly specify obligations of supervisors in self-construction and also provide sanctions, are critically discussed. Construction is always accompanied by various interests and the legislator must ensure minimal safety and construction standards, as well as living standards for all single-family houses, in order to ensure socially responsible actions of all participants in a project. In practice the status and role of the supervisor from the investor’s point of view is not clear.